Hardware and Software Complex for the Study of the Joint Use of Technical Means Based on Various Physical Principles - E. I. Mikhnionok; A. V. Khizniak (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
The article considers the hardware and software complex developed by the authors for the study of the joint use of technical means built on various physical principles. This hardware and software complex is a set of jointly functioning security equipment (optoelectronic system, seismic sensors, fiber-optic sensors) that solve the problem of automatic detection of moving objects in a given area of space. The hardware and software complex is based on the technical observation post developed by the authors, which provides solutions to the problems of automatic detection of moving objects in the field of view of the system sensors, as well as joint functioning with other technical means of protection. Its features and capabilities are described. The results of evaluating the effectiveness of the implementation of the developed hardware and software complex in the integrated security system are presented, using the example of one of the state border protection units. The effect is to reduce the probability of an error when making a decision about the presence of a “real” violator, as well as to increase the probability of their detection. The results of field tests of the hardware and software complex in real operating conditions on the state border section are presented.